Dupilumab safety and efficacy in uncontrolled asthma: a systematic review and meta-analysis of randomized clinical trials. (3rd October 2019) - Zayed, Yazan; Kheiri, Babikir; Banifadel, Momen; Hicks, Michael; Aburahma, Ahmed; Hamid, Kewan; Bachuwa, Ghassan; Chandran, Arul
Abstract: Objective : We aimed to perform a meta-analysis evaluating the efficacy and safety of dupilumab in patients with uncontrolled asthma. Data source : A search of electronic databases was performed using PubMed, Cochrane library and Embase. Study selection : The literature search was conducted independently by two reviewers. Only randomized controlled trials (RCTs) that compared between placebo and dupilumab in patients with uncontrolled asthma were included in this analysis. Pooled risk ratios (RRs) and mean differences (MDs) with their corresponding 95% confidence intervals (CIs) were calculated for dichotomous and continuous data, respectively. Results : A total of four RCTs representing 2, 992 patients were included. Pooled analysis showed significant reductions of the annualized rate of severe asthma exacerbation in the dupilumab group compared with placebo (RR 0.44; 95% CI 0.35–0.055; P < 0.01; I2 = 42%). In addition, the absolute forced expiratory volume at 1 s (FEV1) changes were significantly increased for the dupilumab group (MD 0.14; 95% CI: 0.12–0.17; P < 0.01; I2 = 0%). Finally, there were no significant differences between both groups in the development of any adverse event, serious adverse events, adverse events leading to death, discontinuation of medication due to adverse event or the occurrence of upper respiratory tract, influenza or bronchitis infections. However, dupilumab was associated with an increased risk of injection site reactions compared with placebo (RR 1.91; 95% CI 1.41, 2.59; P < 0.01; I2 = 24%). Conclusion : Among patients with uncontrolled asthma, the addition of dupilumab was associated with a reduced risk of severe asthma exacerbations and improvement in FEV1 without an increased risk of adverse events apart from injection site reactions with dupilumab.